Effect of magnetic field on the formation of Cu nanoparticles during magnetron sputtering in the gas aggregation cluster source. Issue 11 (7th August 2019) - Vaidulych, Mykhailo; Hanuš, Jan; Kousal, Jaroslav; Kadlec, Stanislav; Marek, Aleš; Khalakhan, Ivan; Shelemin, Artem; Solař, Pavel; Choukourov, Andrei; Kylián, Ondřej; Biederman, Hynek
Abstract: Reliable production of nanoparticles (NPs) by magnetron sputtering in a gas aggregation source (GAS) is of great interest because of many potential applications. The size, shape, or structure of NPs can be tuned by the operational parameters of the GAS. In this study, fabrication of copper (Cu) NPs is investigated dependent on the magnetron magnetic field (MF)–a not much studied parameter. Decrease of the MF from 83 to 35 mT results in changes in the shape and size distribution of the NPs. MF also strongly affects the NPs deposition rate (DR). Electromagnetic trapping of the NPs in the vicinity of the magnetron target is proposed to be responsible for the changes in DR and polydispersity. The highest DR was reached at 45 mT. Abstract : The magnetron magnetic field (MF) has a strong influence on the formation and growth of copper nanoparticles (Cu NPs) during the fabrication in a gas aggregation source. The size, shape, and deposition rate of Cu NPs is affected when decreasing the MF from 83 to 35 mT (the magnet‐to‐target distance of 0–6 mm).